(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2025)
The demand for bioresorbable, patient-specific implants has increased interest in additive manufacturing techniques capable of processing biodegradable metals. This work explores the use of Molten Metal Jetting (MMJ) for fabricating porous zinc scaffolds, aiming to develop customized degradable structures for biomedical applications. Zinc is a promising candidate due to its moderate degradation rate and essential biological function in human metabolism. However, its implementation through MMJ remains unexplored [1], [2]. This study uses magnetohydrodynamic (MHD) actuation forces to eject molten zinc droplets towards a moving substrate to form the desired 3D shape. This approach allows precise control over droplet formation and ejection. The influence of jetting parameters is currently being investigated. This early study examines how MMJ jetting parameters, such as firing frequency and drop spacing, affect the printed structures. The effect of these variables on the percentage of porosity, the pore size, and degradation behavior are analyzed [3]. Printed structures were characterized using micro-computed tomography (?CT), revealing average porosity values ranging from 3.5% to 12%, with pore diameters between 95 and 650 µm. In vitro degradation testing was conducted in cell culture media over 72 hours in a dissolution machine. During this period, the pH of the media decreased from 7.4 to 6.2 ± 0.3, and cumulative zinc ion release reached 5.6 ± 0.4 mg/L. Scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS) analyses confirmed localized corrosion and the formation of ZnO-rich surface layers. Three-dimensional reconstruction of the specimens confirmed this result by comparing the initial and final scaffold geometries. These initial findings demonstrate that MMJ additive manufacturing can potentially enable the fabrication of zinc scaffolds with tunable porosity and predictable degradation behavior. References [1] H. Kabir, K. Munir, C. Wen, and Y. Li, “Recent research and progress of biodegradable zinc alloys and composites for biomedical applications: Biomechanical and biocorrosion perspectives,” Bioact Mater, vol. 6, no. 3, pp. 836–879, 2021, doi: 10.1016/j.bioactmat.2020.09.013. [2] Y. Li et al., “Additively manufactured biodegradable porous zinc,” Acta Biomater, vol. 101, pp. 609–623, 2020, doi: 10.1016/j.actbio.2019.10.034. [3] M. Meda, P. Mehta, C. Mahajan, B. Kahn, and D. Cormier, “Magnetohydrodynamic liquid metal droplet jetting of highly conductive electronic traces,” Flexible and Printed Electronics, vol. 6, no. 3, 2021, doi: 10.1088/2058-8585/ac0fee.